Capturing Beneficial Changes to Racehorse Veterinary Care Implemented during the COVID-19 Pandemic - Butler, Deborah (Animals (Basel), 2021)
SIMPLE SUMMARY: On 23 March 2020, the UK Government introduced its first nationwide lockdown as part of efforts to reduce the impact of COVID-19. There have since been two more. “Lockdown” control measures meant both racehorse trainers and veterinary surgeons (vets) had to make changes to the way they worked. Beneficial practices which aided veterinary care have been reported anecdotally, as has an increase in the use of electronic communication and information technologies. The aim of this study was to investigate if these claims could be supported by exploring any changes to racehorse veterinary care that occurred due to the implementation of the first COVID-19 lockdown restrictions. Data collection involved carrying out ten semistructured interviews with racehorse trainers and ten equine vets from November 2020 to January 2021. Reflexive thematic analysis was used to try and make sense of how vets and trainers interacted with each other before and during a period of rapid change and how both groups found alternative ways to ensure beneficial veterinary care was not compromised. Data Analysis revealed four themes threading through the data. These were, firstly, the trainer–vet relationship is built upon a good working relationship, secondly, there had been little or no change in the vet–trainer relationship during the first “lockdown” period. Thirdly, when COVID-19 restrictions were in force, more remote consultations took place using images or videos as well as telephone consults, and the fourth and final theme identified the way connectivity and poor-quality images and videos limited their effectiveness. ABSTRACT: In March 2020, the World Health Organisation called for countries to take urgent and aggressive action against a global pandemic caused by COVID-19. Restrictions were introduced in many countries to reduce transmission of COVID-19 and ultimately deaths. Such restrictions have been colloquially referred to as “lockdown”. Anecdotal evidence of the beneficial practices that facilitated safe veterinary treatment and equine care had been reported together with an increase in the use of electronic communication and information technologies during the first “lockdown”. Thus, the aim of this qualitative study was to capture any beneficial changes to racehorse veterinary care that were implemented during the first “lockdown” period in the UK that lasted from 23 March to 12 May 2020. Ten equine veterinary surgeons who primarily treat racehorses and 10 racehorse trainers were interviewed either by telephone or by videoconferencing. After using thematic analysis from a critical realist social constructionist perspective, four themes were identified. These were, firstly, according to our participants, the trainer–vet relationship is predicated upon a good working relationship, secondly, there had been little or no change in the vet–trainer relationship during the first “lockdown” period. Thirdly, when COVID-19 restrictions were in force, more remote consultations took place using images or videos as well as telephone consults, viewed favourably by both trainers and vets, and finally, intermittent connectivity and poor-quality images and videos limited their effectiveness. In order to fully benefit from the positive changes employed by some vets and trainers in their working relationships, we recommend that rural connectivity is prioritised.